Efecto de antioxidantes naturales en dieta sobre los parámetros productivos de pollos de engorde línea COBB 500 - Ponce Lecca, Ever Henry (2017)
In order to evaluate the effects of supplementation of natural antioxidants (AN) based on thistle extract (Silybum marianum) and ginger (Zingiber officinale) added in drinking water, on the production parameters of broilers meat line Cobb 500 in a period of 42 days of aging, in the locality of La Esperanza, a control treatment without AN (T0), with 1 ml of AN / liter of water (T1) and with 2 ml of AN / liter of water (T2) with three replicates per treatment, each with twenty experimental units evaluated with completely randomized design (DCA). The variables evaluated were weight gain, final weight, feed intake, feed conversion and productive efficiency index. The results in increase of total weight (Kg) and feed conversion were for T2 with 2,897 and 2,09; then T1 with 2,877 and 2.10 and T0 with 2,847 and 2.14 respectively, without statistical differences between treatments; in terms of the productive efficiency index, the best was the T2 with 334.93, achieving 4.16% more than the T0; It was concluded that the use of natural extracts in the raising of broiler chickens improves the productive parameters although no statistical differences were found, the numerical difference is important, taking into account the large number of birds that are raised in each season.